Mental disorders in cervical dystonia – clinical heterogeneity, impact on disease severity and quality of life - A. A. Ragimova; D. S. Petelin; T. Y. Avseytseva; M. A. Samushia; A. F. Ivolgin (Неврология, нейропсихиатрия, психосоматика)
Objective: to establish the clinical structure of mental disorders in patients with verified diagnosis of cervical dystonia (CD), as well as their impact on the severity of a neurological disease and quality of life.Patients and methods. 43 patients (35 women, 8 men, mean age 40.67±10.4 years) with primary CD were examined using clinical and psychopathological methods, i.e. anamnestic data and psychometric methods (CDQ24, HADS, PSQI, TAS, SF-36).Results and discussion. Four groups of patients were distinguished: 1) without mental pathology, 2) with conversion and dissociative symptoms, 3) with social phobia, and 4) with a history of psychotic episodes. It was shown that the severity of CD increased in the row of the described groups, however, psychopathological symptoms determined the severity of CD only in patients with social phobia and psychotic episodes. The only predictor of a decrease in the mental component of quality of life was a high level of anxiety.Conclusion. Some patients with CD have comorbid mental disorders that require psychotherapeutic and psychopharmacological assistance.